Mice deficient in complement C3 are protected against recognition memory deficits and astrogliosis induced by status epilepticus - Schartz, Nicole D.; Aroor, Alisha; Li, Yibo; Pinzón-Hoyos, Nicole; Brewster, Amy L. (Frontiers in Molecular Neuroscience, 2023)
Introduction Status epilepticus (SE) can significantly increase the risk of temporal lobe epilepsy (TLE) and cognitive comorbidities. A potential candidate mechanism underlying memory defects in epilepsy may be the immune complement system. The complement cascade, part of the innate immune system, modulates inflammatory and phagocytosis signaling, and has been shown to contribute to learning and memory dysfunctions in neurodegenerative disorders. We previously reported that complement C3 is elevated in brain biopsies from human drug-resistant epilepsy and in experimental rodent models. We also found that SE-induced increases in hippocampal C3 levels paralleled the development of hippocampal-dependent spatial learning and memory deficits in rats. Thus, we hypothesized that SE-induced C3 activation contributes to this pathophysiology in a mouse model of SE and acquired TLE. Methods In this study C3 knockout (KO) and wild type (WT) mice were subjected to one hour of pilocarpine-induced SE or sham conditions (control; C). Following a latent period of two weeks, recognition memory was assessed utilizing the novel object recognition (NOR) test. Western blotting was utilized to determine the protein levels of C3 in hippocampal lysates. In addition, we assessed the protein levels and distribution of the astrocyte marker glial fibrillary acidic protein (GFAP). Results In the NOR test, control WT + C or C3 KO + C mice spent significantly more time exploring the novel object compared to the familiar object. In contrast, WT+SE mice did not show preference for either object, indicating a memory defect. This deficit was prevented in C3 KO + SE mice, which performed similarly to controls. In addition, we found that SE triggered significant increases in the protein levels of GFAP in hippocampi of WT mice but not in C3 KO mice. Discussion These findings suggest that ablation of C3 prevents SE-induced recognition memory deficits and that a C3-astrocyte interplay may play a role. Therefore, it is possible that enhanced C3 signaling contributes to SE-associated cognitive decline during epileptogenesis and may serve as a potential therapeutic target for treating cognitive comorbidities in acquired TLE.